AI Service Quality and Brand Image in Shaping Gen Z’s Purchase Intention on Traveloka: The Mediating Role of Customer Engagement - Dandi Karepsina; Yandri Samuel Augusteyn; Sardina Sobeukum (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2026)
Objective – This study aims to analyze the influence of AI Service Quality and Brand Image on Generation Z’s Purchase Intention on the Traveloka platform, with Customer Engagement as the mediating variable. Design/Methodology/Approach – The study employs a quantitative approach using an explanatory method. Data were collected via an online questionnaire administered to 370 Generation Z respondents in Surabaya using purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via the SmartPLS 4 software. Findings – The results indicate that AI Service Quality does not have a direct effect on Purchase Intention but exerts a very strong influence on Customer Engagement. Brand Image was found to have a significant effect on both Purchase Intention and Customer Engagement. Furthermore, Customer Engagement has a significant positive effect on Purchase Intention and acts as a full mediator in the relationship between AI Service Quality and Purchase Intention, as well as a partial mediator in the relationship between Brand Image and Purchase Intention. Implications – These findings confirm that the effectiveness of AI is determined not only by technical capabilities but also by its ability to foster emotional engagement. Practically, companies need to integrate technological quality with a relational approach to enhance user loyalty and purchase intention.